PENGARUH KADAR ASAM OLEAT, ISOPROPIL ALKOHOL, DAN PROPILEN GLIKOL TERHADAP KARAKTERISTIK FISIKOKIMIA PATCH KALIUM LOSARTAN DENGAN POLIMER MATRIKS HYDROXYPROPYL METHYLCELLULOSE DAN POLYVYNIL ALCOHOL BESERTA PROFIL TRANSPOR TRANSDERMAL IN VITRO - , RINA WIDIASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Losartan, one of the potent angiotensin II receptor antagonist has a low bioavailability (33%) due to intensive metabolism in the liver. Therefore, the transdermal delivery system could be one alternative efforts to improve the bioavailability of the drug. The aimed of this study was to determine the effect of oleic acid, isopropyl alcohol, and propylene glycol on the physicochemical characteristics of the patch with hydroxypropyl methylcellulose (HPMC) and polyvynil alcohol (PVA) polymer matrix as well as to characterize the profile of transdermal transport in vitro. Oleic acid, isopropyl alcohol, propylene glycol and its composition is determined by the simplex lattice design approach. Physicochemical characteristics including thickness, weight, loss on drying, moisture uptake, folding endurance, drug content, as well as the evaluation of the visual impression of the patch were evaluated. Transdermal transport was`evaluated in vitro using vertical diffusion cell. Concentrations of losartan transport were determined using HPLC method. WinSAAM software was used to analyze the transport data based on compartemental method. The results showed a combination of oleic acid, isopropyl alcohol, and propylene glycol in the matrix polymer of HPMC and PVA can be made adequate patch and enhancers have an influence on the physicochemical characteristics of losartan kalium patch. Optimum condition of patches had 2.3% of oleic acid, 4.2% isopropyl alcohol, and 9.5% of propylene glycol with the characteristic thickness (0.628 ± 0.00) mm, weights patch (131.37 ± 0.84) mg, loss on drying (16,8 ± 1.31)%, moisture uptake (10.91 ± 0.41)%, drug content (100.0 ± 0.78)%, and folding endurance > 300. Transport of losartan was adequately described by a four-compartement model. Losartan have transported at the 11th hours since the patch was applied. Predicted plasma drug could reach a level of 0.6 ng / mL when a 2.01 cm2 patch was used after 56 hours.